A formação do professor de educação física no Pará: o que revela a história do currículo do curso de educação física da Universidade Estadual do Pará? - TREPTOW, Anahy Garcia (2008)
This research has the aim of analyzing the history of the curriculum of the teachers graduation course on Physical Education at the Federal University in Pará, from 1970 to 2007. It was used, as a method of work, the documentary research based on the analysis of the regiments, curricular matrices, and Pedagogical Political Project (PPP) of the Federal University of Pará, and the resolutions of the Federal Council of Education n 69/1969, that determined the minimum curriculum, created the Physical Education‟s Major, and kept the sporting technician; the Resolution CFE n 3/87, that preconized the Major degree and/or BA; the Resolution CNE/CES n 7/2004, that instituted the Curricular Policies for the Graduation Courses in Physical Education; the Resolution n1/2002, that deals with the Curricular Policies for the courses of Elementary School Teachers (superior level, major degree); the Resolution n 2/2002, that institutes the length of the Major Courses in Elementary School Teaching. It was verified that the course, by its curriculum, can be conceived in two different moments: the first one, before the PPP of 1999, was a sportive conception course and build a professional profile similar to the profile of a sportive technician, non-critical, non-historical; and the second moment, just after the PPP of 1999, the course acquired a brand new conception, directly connected to teaching, expressed in the pedagogical work of different fields, enhancing a professional profile that is broad, generalist, humanist, critical and reflexive, based on ethical, political, and pedagogical principles, on the basis of the scientific rigour.